High-Precision Bill Information Recognition System Based on Image Processing and Convolutional Neural Networks - Johnson, Michael; Zhang, Xue (Journal of Computer Science and Software Applications, 2024)
This study utilizes image processing and deep learning techniques to achieve advanced integration within the project. By employing intelligent image preprocessing, target area localization and segmentation, and CNN-based deep learning for classification and recognition, it enables highly accurate and efficient automated recognition and storage of invoice information. This approach significantly enhances the efficiency of enterprise digitalization in practical applications